2013
DOI: 10.1039/c3dt51502h
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reducing agent, temperature, and substrate topology on diastereoselectivity of the intermolecular coupling reactions, or how “free” are cobalt-complexed propargyl radicals?

Abstract: Applicability of the term "free radical" to organometallic radicals was studied by using the stereoselectivity of radical C-C bond formation as a diagnostic tool. Based on diastereoselectivity data, it was concluded that the reduction of π-bonded, Co2(CO)6-complexed propargyl cations with heterogeneous reducing agents (Zn, Mg) generates "free radicals", while homogeneous reductants (Cp2Co, Na-Ph2CO) produce "sequestered radicals", presumably associated with reductant-derived oxidized species. The latter are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Thus, propargyl radicals generated with either Zn or Mg are the closest to a truly “free radical”. Remarkably, the diastereoselectivities observed for both heterogeneous reductants are close to each other (Zn 84% d , l ; Mg 80% d , l ), further emphasizing the commonality of the species involved. (2) In the case of soluble reductants (Cp 2 Co, Na/Ph 2 CO), the respective oxidized species supposedly remain associated with radicals as a radical-ion pair (entries 3, 4).…”
Section: “Sequestered” Versus “Free” Propargyl Radicalsmentioning
confidence: 62%
See 4 more Smart Citations
“…Thus, propargyl radicals generated with either Zn or Mg are the closest to a truly “free radical”. Remarkably, the diastereoselectivities observed for both heterogeneous reductants are close to each other (Zn 84% d , l ; Mg 80% d , l ), further emphasizing the commonality of the species involved. (2) In the case of soluble reductants (Cp 2 Co, Na/Ph 2 CO), the respective oxidized species supposedly remain associated with radicals as a radical-ion pair (entries 3, 4).…”
Section: “Sequestered” Versus “Free” Propargyl Radicalsmentioning
confidence: 62%
“…Based on the totality of the experimental data, which involves a number of topologically diverse substrates and reducing agents, we concluded that Co 2 (CO) 6 -complexed propargyl radicals, in general, are not kinetically independent species and cannot be categorized as “free”. Their nature depends upon the reducing agents, which in turn can be separated into three distinct categories (Table ): (1) In the case of heterogeneous reductants (Zn, Mg), the precipitation of inorganic salts derived from the reducing agents limits their ability to remain associated with radical species (entries 1, 2).…”
Section: “Sequestered” Versus “Free” Propargyl Radicalsmentioning
confidence: 99%
See 3 more Smart Citations